Method for preparing porous copper foil by electrochemical anodic oxidation in complexing agent electrolyte system

Through electrochemical anodizing method of forming chelates in complexing agent electrolyte, the existing porous copper foil preparation process and poor mechanical integrity of the material are solved, and efficient and low-cost porous copper foil preparation is achieved, which is suitable for advanced electrochemical applications.

CN115261952BActive Publication Date: 2025-03-18QINGHAI INST OF SALT LAKES OF CHINESE ACAD OF SCI
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202210838465.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-07-14
Publication Date
2025-03-18
Estimated Expiration
2042-07-14

AI Technical Summary

Technical Problem

The existing porous copper foil preparation methods require high temperature, high pressure or anhydrous oxygen environment, the preparation process is cumbersome, and the material mechanical integrity is poor, making it difficult to directly apply to the secondary battery or electrocatalytic field.

Method used

Using electrochemical anodization method, a chelate is formed in the complexing agent electrolyte through the coordination of copper ions with the complexing agent, and adsorbed to the anode surface, resulting in partial passivation, and the unpassivated area continues to oxidize to form a porous structure, and porous copper foil is prepared.

Benefits of technology

The preparation of porous copper foil with high specific surface area, high electron transmission efficiency and high strength has been achieved. The operation process is short and the preparation cost is low. It is suitable for the fields of secondary battery current collector and electrocatalysis.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115261952B_ABST
    Figure CN115261952B_ABST
Patent Text Reader

Abstract

The present invention discloses a method for preparing porous copper foil by electrochemical anodization under a complexing agent electrolyte system. The method comprises: providing an electrolyte, the electrolyte mainly comprising a complexing agent electrolyte and an electrolyte additive, the complexing agent electrolyte comprising sodium potassium tartrate, EDTA-2Na, sodium citrate, etc., and the electrolyte additive comprising ammonium sulfate, sodium chloride, ammonia, copper sulfate, sodium hydroxide, sodium sulfate, etc.; using a copper-based metal material as an anode, so that it and a cathode and an electrolyte jointly construct an electrochemical reaction system, and electrochemical anodization is performed to obtain a porous copper foil. The method of the present invention is to anodize the copper foil, and to form a copper chelate with the aid of a complexing agent electrolyte and adsorb it on the anode surface. The method has a short operation process and a low preparation cost, and can prepare a porous copper foil with high specific surface area, high electron transfer efficiency and high strength, and has great application potential in the fields of secondary battery current collectors and electrocatalysis.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing a porous copper foil, in particular to a method for preparing a porous copper foil by electrochemical anodization in a complexing agent electrolyte system and application thereof, belonging to the technical field of copper foil preparation. Background Art

[0002] Copper is widely used in energy storage systems, catalysis, biomedicine, and flexible electrodes due to its excellent electrical conductivity, thermal conductivity, and ductility, as well as being the only single metal that can catalyze CC coupling. In order to make copper foil have more efficient electrochemical performance, copper foil is designed as a porous structure, which can significantly improve its potential in advanced electrochemical applications such as secondary batteries and electrocatalysis. For example, in secondary batteries, the copper foil current collector is designed as a porous structure. Its large specific surface area not only reduces the local current density and inhibits the growth of metal dendrites; at the same time, the porous channels can also alleviate the huge volume changes of metal active materials during the deposition / stripping process. It is reported that copper-based catalysts have high selectivity for multi-carbon products in the CO2 reduction process. By making its surface nanoporous and rich in electrocatalytic active sites, the Faraday efficiency in the CO2RR process can be significantly improved.

[0003] Existing methods for preparing porous copper foil usually require high temperature, high pressure or anhydrous oxygen environment, and the preparation process is cumbersome; the preparation conditions such as template method, powder sintering method, and dealloying method are harsh, and the material samples are generally in powder form or incomplete blocks, with extremely poor mechanical integrity, which makes it difficult to directly apply such materials to the copper foil current collector process produced by roll-to-roll production or complete electrocatalysts. In current applications, the strength support phase substrate and porous copper are generally compounded to obtain a porous copper composite material with good mechanical integrity for application. This not only further complicates the sample preparation process and increases the preparation cost, but also reduces the conductivity of the porous copper itself, limiting the further development of porous copper foil. Summary of the invention

[0004] The main purpose of the present invention is to provide a method for preparing porous copper foil by electrochemical anodization and its application, so as to overcome the shortcomings of the prior art.

[0005] In order to achieve the above-mentioned object of the invention, the present invention adopts the following technical solutions:

[0006] The embodiment of the present invention provides a method for preparing a porous copper foil by electrochemical anodization, which comprises:

[0007] Providing an electrolyte, the electrolyte mainly comprising a complexing agent electrolyte and an electrolyte additive that is optionally added or not added,

[0008] The complexing agent electrolyte includes any one of potassium sodium tartrate, EDTA-2Na, and sodium citrate, or a combination of two or more thereof; the electrolyte additive includes any one of ammonium sulfate, sodium chloride, ammonia water, copper sulfate, sodium hydroxide, and sodium sulfate, or a combination of two or more thereof;

[0009] A copper-based metal material is used as an anode, and an electrochemical reaction system is constructed together with a cathode and an electrolyte to perform electrochemical anodic oxidation to obtain a porous copper foil.

[0010] In some embodiments, the concentration of the complexing agent electrolyte is 0.01-0.3 mol / L.

[0011] Furthermore, the concentration of the electrolyte additive is below 0.2 mol / L.

[0012] In some embodiments, the current density used in the electrochemical anodization is in the range of 0.01 A / cm 2 ~0.5A / cm 2 , time is 3 to 90 minutes.

[0013] The embodiment of the present invention also provides a porous copper foil made by the above method.

[0014] The embodiment of the present invention also provides the application of the aforementioned porous copper foil in the fields of secondary battery current collector preparation or electrocatalysis.

[0015] Compared with the traditional preparation and application methods of porous copper, the present invention proposes a simple and efficient preparation idea for porous copper foil. By anodizing the copper foil, in a selected complexing agent electrolyte, copper ions coordinate with the complexing agent to form a chelate that is adsorbed to the anode surface, resulting in partial passivation of the copper foil surface. The unpassivated area forms a pore structure due to continued oxidation, and finally a copper foil with a porous structure is prepared by controlling the current density and oxidation time. The method has a short operation process and low preparation cost, and avoids the poor conductivity of the sample and the cumbersome preparation process caused by the use of binders or composite materials. The method can prepare porous copper foil with high specific surface area, high electron transfer efficiency and high strength, and has great application potential in the fields of secondary battery current collectors, electrocatalysis, etc. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0017] Figure 1Schematic diagram of a method for preparing a porous copper foil by electrochemical anodization in a typical embodiment of the present invention;

[0018] Figure 2 This is the SEM microstructure of a commercial 11μm flat copper foil;

[0019] Figure 3 is a SEM microstructure image of the porous copper foil prepared in Example 1 of the present invention;

[0020] Figure 4 This is the XRD diagram of the porous copper foil prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0021] In view of the deficiencies in the prior art, the inventor of this case has proposed the technical solution of the present invention after long-term research and extensive practice, providing a method for preparing porous copper with simple operation, low cost, no need for adhesives / composite materials, high strength and good conductivity, mainly through anodizing the copper foil and supplemented with a special complexing agent electrolyte to form a copper chelate, and finally preparing a copper foil with a porous structure. The technical solution, its implementation process and principle will be further explained as follows.

[0022] One aspect of an embodiment of the present invention provides a method for preparing a porous copper foil by electrochemical anodization, which is prepared by electrochemical anodization and supplemented by electrolyte complexation of copper ions, and mainly includes:

[0023] Providing an electrolyte, the electrolyte mainly comprising a complexing agent electrolyte and an electrolyte additive that is optionally added or not added, the complexing agent electrolyte including but not limited to any one or a combination of two or more of potassium sodium tartrate, EDTA-2Na, sodium citrate, etc.; the electrolyte additive including but not limited to any one or a combination of two or more of ammonium sulfate, sodium chloride, ammonia water, copper sulfate, sodium hydroxide, sodium sulfate, etc.;

[0024] A copper-based metal material is used as an anode, and an electrochemical reaction system is constructed together with a cathode and an electrolyte to perform electrochemical anodic oxidation to obtain a porous copper foil.

[0025] In the above scheme of the present invention, C4H4O6 2- EDTA 2- and C5H7O5COO - The complexing ions form chelates with copper ions and are partially adsorbed on the surface of copper foil, forming a passivation template on the one hand, and the strong coordination ability prevents copper ions from forming oxide films on the other hand. The addition of electrolyte additives accelerates the reaction rate, and the porous structure can be easily adjusted by accurately adjusting the concentration ratio of the complexing agent and additives.

[0026] The complexing agent electrolyte mainly forms chelates with the copper ions generated by anodic oxidation and adsorbs on the anode surface, thereby passivating part of the anode surface and preventing the copper ions from forming an oxide film. The unpassivated copper foil surface is gradually oxidized to form pores. The electrolyte additive mainly serves to increase the mass transfer rate and electrochemical reaction rate.

[0027] Taking the complexing agent electrolyte as sodium potassium tartrate, EDTA-2Na, etc. as an example, the reaction mechanism of the method for preparing porous copper foil by electrochemical anodization of the present invention can be referred to Figure 1 As shown in the figure, after the copper foil is electrochemically oxidized, the generated copper ions quickly form chelates with the complex ions in the electrolyte without generating an oxide film. The formed chelate is partially adsorbed to the surface of the copper foil to form a passivation template, and the unpassivated area continues to oxidize to form pores, and finally its microscopic morphology is transformed from dense to uniformly dispersed porous. In order to ensure that a sample with mechanical integrity and uniform porous distribution is obtained, the anodization time and current density must be strictly controlled, and the precise control of the electrolyte ratio and temperature is crucial to the generation of a porous structure.

[0028] In some preferred embodiments, the method for preparing porous copper foil by electrochemical anodization may specifically include: using copper-based metal as raw material, first cleaning and pre-treating the copper-based metal; then using the copper-based metal as anode, the Pt sheet as cathode, and potassium sodium tartrate as electrolyte for electrochemical anodization.

[0029] In some preferred embodiments, the concentration of the complexing agent electrolyte is 0.01-0.3 mol / L.

[0030] Furthermore, the concentration of the electrolyte additive does not exceed 0.2 mol / L.

[0031] In some preferred embodiments, the current density used in the electrochemical anodization is in the range of 0.01 A / cm 2 ~0.5A / cm 2 .

[0032] In some preferred embodiments, the electrochemical anodization time is 3 to 90 minutes.

[0033] In some preferred embodiments, the copper-based metal material includes at least any one of planar copper foil, planar crude copper, planar brass material, etc., but is not limited thereto.

[0034] Furthermore, the thickness of the copper-based metal material is generally between 6 and 300 μm.

[0035] In some preferred embodiments, the method for preparing porous copper foil by electrochemical anodization further includes: before electrochemical anodization, the copper-based metal material is first cleaned and pretreated, and the cleaning pretreatment includes ultrasonic cleaning with hydrochloric acid, acetone, and ethanol in sequence for 5 to 15 minutes, wherein the concentration of the hydrochloric acid is 0.03 to 0.5 mol / L.

[0036] Furthermore, the cathode includes a platinum sheet, but is not limited thereto.

[0037] Among them, in some more specific implementation cases, the method for preparing porous copper foil by electrochemical anodization specifically includes the following steps:

[0038] Step 1: Provide a copper-based material of a certain thickness, and use a certain concentration of hydrochloric acid, acetone, and ethanol for ultrasonic cleaning for 5 to 15 minutes to remove surface impurities and oil stains.

[0039] Step 2: Using the obtained pretreated sample as the anode and the Pt sheet as the cathode, anodizing is performed in an electrolyte by controlling the applied voltage and time to obtain a porous copper foil.

[0040] In summary, the method of the present invention has a short oxidation time, a simple electrolyte system, a short operation process and a low preparation cost.

[0041] Another aspect of the embodiment of the present invention further provides a porous copper foil prepared by the above method, wherein the specific surface area is 1.0 to 5.8 m 2 / g, conductivity is 48~70kS / mm, and strength is 80~150Mpa.

[0042] Furthermore, another aspect of the embodiments of the present invention also provides the application of the porous copper foil prepared by electrochemical anodization in the fields of secondary battery current collector preparation or electrocatalysis.

[0043] Through the above technical scheme, the method of the present invention performs anodization on the copper foil. In the selected complexing agent electrolyte, the copper ions coordinate with the complexing agent to form a chelate that is adsorbed to the anode surface, resulting in partial passivation of the copper foil surface. The unpassivated area forms a pore structure due to continued oxidation. Finally, a porous copper foil with a porous structure, high specific surface area, high electron transfer efficiency and high strength is prepared by controlling the current density and oxidation time. The porous copper foil has great application potential in the fields of secondary battery current collectors, electrocatalysis, etc.

[0044] In order to make the purpose, technical scheme and advantages of the present invention clearer, the technical scheme of the present invention is further described in detail below in conjunction with the accompanying drawings and several preferred embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work belong to the scope of protection of the present invention. For the test methods in the following embodiments that do not specify specific conditions, the test methods in the embodiments are all carried out under normal conditions. In addition, the technical features involved in each embodiment of the present invention described below can be combined with each other as long as they do not conflict with each other.

[0045] All reagents used in the following examples were of analytical grade.

[0046] Example 1

[0047] A commercially available flat copper foil with a thickness of 11 μm was selected and ultrasonically cleaned with 0.05 mol / L HCl for 1 min, followed by ultrasonic cleaning with acetone and anhydrous ethanol for 5 min to remove the surface oxide layer and impurities such as oil stains. The surface of the copper foil was rinsed with deionized water for 30 s and quickly dried with N2 for the experiment. First, a porous copper foil was prepared by constant current anodization in a two-electrode system. The pretreated flat copper foil was used as the anode, the platinum sheet as the cathode, and 0.2 mol / L EDTA-2Na as the electrolyte; the current density was set to 0.05 A / cm 2 The anodizing time was 15 min. After the experiment, the samples were simply rinsed with deionized water and quickly dried with N2.

[0048] Figure 2 This is the SEM image of the commercial flat copper foil with a thickness of 11 μm in Example 1. Figure 3 This is the SEM microstructure image of the porous copper foil obtained in Example 1, and the porous structure can be clearly observed. Figure 4 The XRD diagram of the porous copper foil obtained in Example 1 shows that electrochemical anodization has no effect on the crystal structure of the copper foil. The specific surface area of ​​the porous copper foil obtained in Example 1 is 2.65 m 2 / g, conductivity is 56kS / mm, and strength is 103Mpa.

[0049] Example 2

[0050] A commercially available flat copper with a thickness of 40 μm was selected and ultrasonically cleaned with 0.1 mol / L HCl for 3 minutes, followed by ultrasonic cleaning with acetone and anhydrous ethanol for 5 minutes to remove the surface oxide layer and impurities such as oil stains. The copper foil surface was rinsed with deionized water for 30 seconds and quickly dried with N2 for the experiment. First, in a two-electrode system, a porous copper foil was prepared by constant current anodization. The pretreated flat copper foil was used as the anode, the platinum sheet as the cathode, and 0.1 mol / L potassium sodium tartrate and 0.05 mol / L sodium hydroxide as the electrolyte; the current density was set to 0.08 A / cm 2 The anodization time was 30 min. After the experiment, it was briefly rinsed with deionized water and quickly dried with N2.

[0051] Example 3

[0052] A commercially available flat brass with a thickness of 30 μm was selected and ultrasonically cleaned with 0.3 mol / L HCl for 1 min, followed by ultrasonic cleaning with acetone and anhydrous ethanol for 5 min to remove the surface oxide layer and impurities such as oil stains. The copper foil surface was rinsed with deionized water for 30 s and quickly dried with N2 for the experiment. First, in a two-electrode system, a porous copper foil was prepared by constant current anodization. The pretreated flat copper foil was used as the anode, the platinum sheet as the cathode, and 0.05 mol / L potassium sodium tartrate and 0.01 mol / L ammonia water as the electrolyte; the current density was set to 0.06 A / cm 2 The anodization time was 20 min. After the experiment, it was briefly rinsed with deionized water and quickly dried with N2.

[0053] Example 4

[0054] A commercially available flat brass with a thickness of 6 μm was selected and ultrasonically cleaned with 0.5 mol / L HCl for 2 min, followed by ultrasonic cleaning with acetone and anhydrous ethanol for 3 min to remove the surface oxide layer and impurities such as oil stains. The copper foil surface was rinsed with deionized water for 30 s and quickly dried with N2 for the experiment. First, in a two-electrode system, a porous copper foil was prepared by constant current anodization. The pretreated flat copper foil was used as the anode, the platinum sheet as the cathode, and 0.01 mol / L EDTA-2Na as the electrolyte; the current density was set to 0.5 A / cm 2 The anodization time was 3 min. After the experiment, it was briefly rinsed with deionized water and quickly dried with N2.

[0055] Example 5

[0056] A commercially available flat brass with a thickness of 300 μm was selected and ultrasonically cleaned with 0.03 mol / L HCl for 5 minutes, and then ultrasonically cleaned with acetone and anhydrous ethanol for 10 minutes to remove the surface oxide layer and impurities such as oil stains. The copper foil surface was rinsed with deionized water for 30 seconds and quickly dried with N2 for the experiment. First, in a two-electrode system, a porous copper foil was prepared by constant current anodization. The pretreated flat copper foil was used as the anode, the platinum sheet as the cathode, and 0.3 mol / L potassium sodium tartrate as the electrolyte; the current density was set to 0.01 A / cm 2 The anodizing time was 90 min. After the experiment, the samples were simply rinsed with deionized water and quickly dried with N2.

[0057] Comparative Example 1

[0058] This control example is basically the same as Example 1, except that the concentration of EDTA-2Na is 0.4 mol / L.

[0059] Results Since EDTA-2Na could not be completely dissolved, the ionic conductivity of the electrolyte slowed down and a porous structure could not be formed.

[0060] Comparative Example 2

[0061] This comparative example is basically the same as Example 1, except that the electrochemical anodic oxidation current density exceeds 0.5 A / cm 2 Due to the anodic oxidation under high current density, the copper foil samples were severely oxidized partially or completely, unable to retain the overall structure, and produced large cracks and holes.

[0062] Comparative Example 3

[0063] This comparative example is basically the same as Example 1, except that: no complexing agent electrolyte is added, only additive electrolyte is added. Since the copper ions generated by anodization cannot form chelates with the complexing agent, a brown copper oxide passivation film is formed on the surface of the copper foil, and ultimately a porous structure cannot be generated.

[0064] In addition, the inventors of this case also referred to the aforementioned embodiments and conducted experiments with other raw materials, process operations, and process conditions described in this specification, and obtained relatively ideal results.

[0065] Although the present invention has been described with reference to illustrative embodiments, it will be appreciated by those skilled in the art that various other changes, omissions and / or additions may be made and that elements of the described embodiments may be substituted with substantial equivalents without departing from the spirit and scope of the present invention. In addition, many modifications may be made to adapt a particular situation or material to the teachings of the present invention without departing from the scope of the present invention. Therefore, it is not intended herein to limit the present invention to the specific disclosed embodiments for carrying out the present invention, but rather it is intended that the present invention will include all embodiments within the scope of the appended claims.

Claims

1. A method for preparing porous copper foil by electrochemical anodization in a complexing agent electrolyte system, characterized in that: include: Providing an electrolyte, the electrolyte mainly comprising a complexing agent electrolyte and an electrolyte additive that is optionally added or not added, the complexing agent electrolyte comprising any one of potassium sodium tartrate, EDTA-2Na, and sodium citrate or a combination of two or more thereof, the electrolyte additive comprising any one of ammonium sulfate, sodium chloride, ammonia water, copper sulfate, sodium hydroxide, and sodium sulfate or a combination of two or more thereof, the concentration of the complexing agent electrolyte being 0.01 to 0.3 mol / L, and the concentration of the electrolyte additive being below 0.2 mol / L; A copper-based metal material is used as an anode, and an electrochemical reaction system is constructed with the cathode and an electrolyte to perform electrochemical anodic oxidation to obtain a porous copper foil. The current density used in the electrochemical anodic oxidation is 0.01 A / cm 2 ~0.5 A / cm 2 The electrochemical anodization time is 3 to 90 min.

2. The method for preparing porous copper foil by electrochemical anodization in a complexing agent electrolyte system according to claim 1, characterized in that: The copper-based metal material includes at least any one of a planar copper foil, a planar crude copper and a planar brass material.

3. The method for preparing porous copper foil by electrochemical anodization in a complexing agent electrolyte system according to claim 1, characterized in that: The thickness of the copper-based metal material is 6-300 μm.

4. The method for preparing porous copper foil by electrochemical anodization in a complexing agent electrolyte system according to claim 1, characterized in that: Also includes: Before electrochemical anodization, the copper-based metal material is first cleaned and pretreated, and the cleaning pretreatment includes ultrasonic cleaning with hydrochloric acid, acetone, and ethanol in sequence for 5 to 15 minutes, wherein the concentration of the hydrochloric acid is 0.03 to 0.5 mol / L.

5. The method for preparing porous copper foil by electrochemical anodization in a complexing agent electrolyte system according to claim 1, characterized in that: The cathode includes a platinum sheet.

6. The porous copper foil prepared by the method according to any one of claims 1 to 5, wherein the specific surface area is 1.0 to 5.8 m 2 / g, conductivity is 48~70 kS / mm, and strength is 80~150 Mpa.

7. Use of the porous copper foil according to claim 6 in the preparation of secondary battery current collectors or in the field of electrocatalysis.

Citation Information

Patent Citations

  • Electrochemical thermal etching preparation method of microporous battery copper foil and microporous copper foil prepared according to electrochemical thermal etching preparation method

    CN108998826A

  • Preparation method of columnar copper granular film

    CN109082697A